Meta‐gender‐study: A Gender Study of Global Distribution on Gender Studies. Issue 1 (13th October 2021) - Sun, Yinying; Lou, Wen; Zhang, Lin
Abstract: The purpose of this study is to explore the gender distribution of researchers in the field of gender studies. We used bibliometrics methods on a dataset of gender studies from Web of Science between 2007 and 2019. The results show that unlike other fields in scientific communities, gender studies are dominated by female researchers. The majorities of gender study communities come from North America and Europe, which are both dominated by female researchers.